Endothelial nitric oxide synthase polymorphism and venous thromboembolism: A meta-analysis of 9 studies involving 3993 subjects. (December 2021) - Huang, Guangbin; Deng, Xuejun; Xu, Yanan; Wang, Pan; Li, Tao; Hu, Ping
Background: Endothelial nitric oxide synthase (eNOS) polymorphism may influence the risk of venous thromboembolism (VTE). However, data from published studies with low statistical power are inconclusive. The present meta-analysis aimed to assess the relationship between eNOS polymorphism and the risk of VTE. Method: Case-control studies evaluating the association between the eNOS polymorphism and VTE were searched in PubMed, Embase, Web of Science, Google Scholar, Wanfang, Chinese National Knowledge Infrastructure (CNKI), the Chongqing VIP Chinese Science and Technology Periodical Database (VIP), and Chinese Biomedical Literature Database (CBM). Results: A total of 1588 cases and 2405 controls from 9 studies were included in the analysis. The results showed that eNOS G894T polymorphism was related to VTE susceptibility and the difference was statistically significant [T vs G: OR = 1.41, 95% CI (1.13, 1.75), P = 0.002; TT + GG vs TG: OR = 0.71, 95% CI (0.60, 0.84), P = 0.000; TT + TG vs GG: OR = 1.45, 95% CI (1.23, 1.70), P = 0.000]. Additionally, eNOS Intron 4 VNTR polymorphism was related to VTE susceptibility and the difference was statistically significant [4b4b vs 4a4a + 4a4b: OR = 2.77, 95% CI (1.01, 7.61), P = 0.048]. Conclusion: ENOS G894T and eNOS Intron 4 VNTR polymorphisms were associated with VTE susceptibility, especially in Asian populations. However, multicenter studies with larger samples should be conducted to further clarify this association and verify our findings.